PENGARUH KUALITAS PELAYANAN DAN STRATEGI HARGA TERHADAP KEPUASAN PENUMPANG JASA ANGKUTAN UMUM TRAYEK 120 PADA PT. RAHAYU MEDAN CERIA MEDAN - Novien Rialdy (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2017)
AbstractEach firm transportation service providers must act quickly and precisely as a consequence of the internal and external environment changes that occur in the orientation to provide the best service to customers. Companies in the operations must always observe the changes in consumer behavior in order to anticipate changes in the behavior, then reduced to the study in order to improve their marketing strategies. The problem of this research is